Migration and Labour Force Needs in Contemporary Agriculture: What Drives States to Implement Temporary Programs? A Comparison among the Cases of Huelva, Lleida (Spain) and Piana del Sele (Italy) - Molinero-Gerbeau, Yoan; Avallone, Gennaro (Calitatea Vieții, 2018)
During the 1980s, Italy and Spain experienced several political and social changes, including an important demographic shift, passing from being emigration countries to immigration countries. The growth of their economies and their conversion into neoliberalism, structurally transformed the different productive segments, including the agricultural sector that progressively adopted the industrial Californian mode. This transformation required huge amounts of workforce at a time when nationals were abandoning the sector, so growers turned their attention to employ migrant workers, that have become nowadays a structural factor of production in the global agricultural value chains. The ways migrants have been recruited to meet production needs differ from a productive context to another, as it depended on the specific interests and demands of farms operating in each agricultural enclave. This article analyzes, through a comparative perspective, the institutional, legal and informal mechanisms envisaged and implemented in Spain and Italy to encourage the recruitment of foreign workforce, by verifying how and why circular migration programs onto the agricultural sector have been, or not, promoted. To understand how these policies have actually been implemented, three productive enclaves have been compared, Huelva and Lleida, in Spain, and Piana del Sele, in Southern Italy, in order to identify the factors that explain why some agricultural enclaves of the world-ecology have configured systems to import labour from the global periphery, while others have privileged a deregulated model.